Evaluation of the Claria sharesource system from the perspectives of patient/caregiver, physician, and nurse in children undergoing automated peritoneal dialysis - ALPAY, HARİKA (My University, 2023)
Background Automated peritoneal dialysis (APD) is increasingly preferred worldwide. By using a software application (Homechoice with Claria sharesource system (CSS)) with a mod-M added to the APD device, details of the home dialysis treatment become visible for PD nurses and physicians, allowing for close supervision. We aimed to evaluate the perceptions of patients/caregivers, PD nurses, and physicians about the advantages and disadvantages of CSS. Methods Three diferent web-based questionnaires for patients/caregivers, nurses, and physicians were sent to 15 pediatric nephrology centers with more than 1 year of experience with CSS. Results Respective questionnaires were answered by 30 patients/caregivers, 22 pediatric nephrologists, and 15 PD nurses. Most of the nurses and physicians (87% and 73%) reported that CSS improved patient monitoring. A total of 73% of nurses suggested that CCS is not well known by physicians, while half of them reported reviewing CSS data for all patients every morning. Sixty-eight percent of physicians thought that CSS helps save time for both patients/caregivers and healthcare providers by reducing visits. However, only 20% of patients/caregivers reported reduced hospital visits. A total of 90% of patients/caregivers reported that being under constant monitoring made them feel safe, and 83% stated that the patient’s sleep quality improved. Conclusions A remote monitoring APD system, CSS, can be successfully applied with children for increased adherence to dialysis prescription by giving shared responsibility and may help increase the patient’s quality of life. This platform is more commonly used by nurses than physicians. Its potential benefts should be evaluated in further well-designed clinical studies with larger patient groups.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Nephrology; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Pediatri; Üroloji; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Urology; Pediatrics, Perinatology and Child Health; Peritoneal dialysis; Remote monitoring; Children; Quality of life; HEALTH-CARE NEEDS; HEMODIALYSIS; SURVIVAL; TELEMEDICINE; TELEHEALTH; EXCHANGES; IMPACT; CAPD; Peritoneal dialysis; Remote monitoring; Quality of life